Classification of Simple Weight Modules over the Schrödinger Algebra. Issue 1 (1st March 2018) - Bavula, V. V.; Lu, T.
Abstract: A classification of simple weight modules over the Schrödinger algebra is given. The Krull and the global dimensions are found for the centralizer C_S(H) (and some of its prime factor algebras) of the Cartan element H in the universal enveloping algebra S of the Schrödinger (Lie) algebra. The simple C_S(H) -modules are classified. The Krull and the global dimensions are found for some (prime) factor algebras of the algebra S (over the centre). It is proved that some (prime) factor algebras of S and C_S(H) are tensor homological / Krull minimal.